THE IMPACT OF AUDIT QUALITY ON THE RELEVANCE OF ACCOUNTING INFORMATION'S VALUE THROUGH MEDIATING ROLE OF EARNINGS MANAGEMENT PRACTICE - Jalil Ibrahim Salih; Abdulhussain Tofeeq Shibli (Scholars Digest Publishing, 2024)
This study aims to measure the impact of changing the auditor and the quality of the audit on the appropriateness of the value of accounting information in Iraqi banks listed on the Iraq Stock Exchange. The research sample included 19 Iraqi banks listed on the Iraq Stock Exchange from (2014 to 2022) with 171 annual observations obtained from the financial reports of these banks published on the Iraq Stock Exchange website. In analyzing the data, the researcher relied on the statistical packages (SPSS 28) and the statistical package (STATA 17), and the researcher concluded that audit fees have a direct negative impact on earnings management. At a level of statistical significance (1%), on the other hand, the size of the auditing firm had a positive effect on earnings management. There is a direct negative effect of earnings management on the suitability of the value to earnings per share and the suitability of the value to the book values of Iraqi banks listed on the Iraq Stock Exchange. There is a direct positive effect of audit quality represented by the two variables (audit fees and size of the audit firm) on the relevance of accounting information's value.
Keywords: Audit Quality; Relevance of Accounting Information; Earnings Management.